2021
DOI: 10.1126/sciadv.abe7804
|View full text |Cite
|
Sign up to set email alerts
|

SMARCAD1-mediated active replication fork stability maintains genome integrity

Abstract: The stalled fork protection pathway mediated by breast cancer 1/2 (BRCA1/2) proteins is critical for replication fork stability. However, it is unclear whether additional mechanisms are required to maintain replication fork stability. We describe a hitherto unknown mechanism, by which the SWI/SNF-related matrix-associated actin-dependent regulator of chromatin subfamily-A containing DEAD/H box-1 (SMARCAD1) stabilizes active replication forks, that is essential to maintaining resistance towards replication pois… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…It may be involved in dermatoglyph and sweat gland development by regulating the expression of epidermal differentiation-associated genes [ 16 ]. In addition, it also plays an import role in repairing potentially lethal DNA double-strand breaks [ 13 ] and maintaining genome integrity by stabilizing active replication [ 17 ]. Multiple studies have demonstrated that break points and mutations of the gene are involved in several human diseases, such as genodermatosis [ 5 , 18 , 19 ], malignant peripheral nerve sheath tumors [ 20 ], breast cancer [ 17 ], and pancreatic cancer [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may be involved in dermatoglyph and sweat gland development by regulating the expression of epidermal differentiation-associated genes [ 16 ]. In addition, it also plays an import role in repairing potentially lethal DNA double-strand breaks [ 13 ] and maintaining genome integrity by stabilizing active replication [ 17 ]. Multiple studies have demonstrated that break points and mutations of the gene are involved in several human diseases, such as genodermatosis [ 5 , 18 , 19 ], malignant peripheral nerve sheath tumors [ 20 ], breast cancer [ 17 ], and pancreatic cancer [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…No significant reduction in the IdU track could be observed, which would have been expected if the forks underwent degradation (Figures 5C and S5E). Together, these data suggest that heat stress impacts active, ongoing, and restarted replication fork stability (Lo et al, 2021) but not stalled fork protection (Schlacher et al, 2012). We have previously reported the involvement of MOF in suppression of replication stress (Singh et al, 2018) and, therefore, determined if MOF depletion and hyperthermia have a synergistic effect on replication stress.…”
Section: Heat-shock Impairs Dna Replication Fork Progression and Rest...mentioning
confidence: 77%
“…Interestingly, in fission yeast, Fft3 is shown to suppress histone turnover at heterochromatin regions to ensure the correct propagation of parental nucleosomes. Fft3 was further shown to suppress histone turn-over at difficult-to-replicate regions in order to preclude RNA:DNA hybrid formation that can lead to impaired fork progression [176]. It was suggested that in absence of Fft3, the enhanced turn-over leads to an open chromatin structure that facilitates R-loop formation at specific loci of the genome, especially those that are highly transcribing and/ or contain intragenic repetitive sequences [176].…”
Section: Brg1mentioning
confidence: 99%
“…More recently SMARCAD1 is shown to mediate a novel pathway of active replication fork stability by maintaining PCNA homeostasis at forks, distinct from BRCA-mediated stalled fork protection pathway [176]. Given that many of the factors discussed, apart from having a role in DNA breaks repair also have a role in replication fork stability and remodeling pathways [176,[236][237][238][239][240][241], it is possible that chromatin remodelers such as SMARCAD1 could have a role in the resolution of R-loops, as previously suggested in the fission yeast ortholog Fft3 [175]. Moreover, since SMARCAD1 travels with the replisome, its action could regulate R-loop resolution ahead of the fork, an interesting possibility that is yet to be tested.…”
Section: Brg1mentioning
confidence: 99%